Pemanfaatan Cendawan Mikoriza Vesikular Arbuskular (CMA) dalam pembibitan tanaman kopi (Coffea robusta L.) pada Ultisol - Badal, Bustari; Karimi, Syafruddin; Febriansyah, Rudi; Munzir, Abdullah (Fakultas Pertanian Universitas Tamansiswa Padang, 2009)
The Research conducted about exploating of Fungi Mycorrhiza Vesicular Arbuskular(CMA) to growth of Coffee seed (Coffea robusta L) at Ultisol soil. Aim to know some measuring of appropriate CMA in improving growth of seed Cowpea. This research use complete Randomized Design (CRD) with 6 treatmens and 4 replication. Data was analyzed by ANOVA and DNMRT. The treatmens were amount of CMA used in Coffe plant : A0 (0g polybag-1), A1 (20 g polybag-1), A2 (40 g polybag-1), A3 (60 g polybag-1), A4 (80 g polybag-1), A5 (100 g polybag-1). The result showed that increasing of CMA dose will increased growth of Coffee.